Response of GUEST to Manning's n at steep slope - Nuevo, Riche U. (Philippine Agricultural Mechanization Journal, 2008)
The response of the Griffith University Erosion System Template (GUEST), a physical process-oriented water-induced soil erosion model to Manning's roughness coefficient n was evaluated at the 60% slope bare runoff plot of the Department of Agricultural Engineering of the Visayas State University (VSU), Baybay City, Leyte. Ten (10) different values of n from 0.03 to 0.12 (at 0.01 interval) and 32 recorded storm events were used in the analysis. The average sediment concentration at the transport limit (ct), saltation shear stress (tsa), saltation shear stress o total shear stress ratio (tsa/t), and saltation shear stress to surface shear stress ratio (tsa/ts) were computed using the new GUEST erosion theory for shallow flows and high sediment concentrations. The results showed that all modeled parameters have a general inverse relationship to n and that variations were magnified during rilled storm events and at high values of n. A curve-fitting analysis was done to express the modeled parameters as a function of n. The results showed that all parameters were consistently of the power form y=an^b where y is the modeled parameter, n is Manning's roughness coefficient and a and b are constants. The results also showed that b<0 and R^2 is approximately equal to one. Rilled storm events displayed slightly lower values of R^2 probably due to inaccuracies in estimating rill geometry. Curve-fitting analysis of the stress ratios against ct at different values of n showed that the curve of the best fit was also of the power y=ax^b with the stress ratios directly related to ct. The tightness of the curve of best fit increased as n increased. Statistical analysis using RCBD showed that the modeled parameters were significantly affected by n. Further test using DMRT showed that the treatment means at low values of n (0.03 to 0.06) differed significantly from each other.